Global Financial Meltdown and its Impact on the Indian Financial System - Maruti Rao, N.; Naikwadi, Iftikar M. (Indian Journal of Finance, 2009)
Today, world economy is under tremendous pressure. Such pressure was never been seen since last seven decades. Governments and central banks of respective countries world over have initiated various measures on war footing to mitigate the impact of global financial meltdown such as injecting liquidity through financial packages into the system in order to revive ever nose diving economy. The impact of global financial meltdown can also be seen on Indian economy in general and financial system in particular. BSE Sensex, the mirror of Indian economy has crashed and slipped to less than 10000 points from its peak of 21000. The Indian corporate world has resorted to production cut, shut down and job cut as a measures to fight out impact of global financial meltdown (GFM). To cope with ever growing pressure of GFM the government of India and RBI have taken various measures to bring down the impact of global financial meltdown on Indian economy which include cut in Cash Reserve Ratio (CRR), Statutory Liquidity Ratio (SLR), repo and reverse repo rates, extension of duty drawback scheme, etc. The tentacle of GFM has not only taken Indian economy into its clutches, even society is not outside its grip. The prime focus of this study is to know impact of global financial meltdown on Indian financial system in general and stock prices of few selected Indian companies in particular. The study also intends to look into the impact of GFM on Banking, Insurance and Mutual Fund (MFs) industries. Further, the study will investigate the impact of GFM on corporate fund raising. The study also suggests suitable strategies to minimize impact of GFMs on Indian financial system.